Untitled - Hien, Le Xuan; Vuong, Nguyen Thien; Viet Trieu, Nguyen Thi; Thuong, Ngo Hanh (Vietnam Journal of Science and Technology, 2015)
The influence of the content of cobalt naphthenate accelerator on the crosslinking process of the curable system on the base of vinyl ester of epoxy-diane resin and styrene system has been studied. It was determined by IR – spectroscopic study that acrylate and styrene double bonds sharply decreased during the curing process. The participation of the double bonds to the crosslinking polymerization led to the gelation and change of physico – mechanical properties of the vinyl ester – styrene system. The change ofmass ratio of the accelerator / resin system from 0.025 to 0.1 % resulted in decrease of the gelation time, swelling degree and increase of the gel fraction, hardness of the cured coatings.